A POSTCOLONIAL VALUES ANALYSIS OF ENGLISH TEXTBOOKS IN SECOND GRADES SENIOR HIGH SCHOOL: Analisis nilai poskonolonial dalam buku Bahasa Inggris kelas 2 SMA - Budik Kusworo (IAI Al-Qolam, 2021)
The aims of this study are to find out some postcolonial values in English textbooks second grades, they are: (1) Western Superiority, (2) Eastern Subordination, and (3) Mimicry.This research is a qualitative descriptive study focusing on library research. The object of research is an English textbook which includes: (1) Pathway to English by Erlangga Publisher, (2) Talk Active by Yudhistira Publisher, and (3) Bahasa Inggris by the Ministry of Education and Culture (Kemendikbud). The results of this study are found Western Superiority, Eastern Subordination and Mimicry (as postcolonial forms) of English Textbooks. The forms are Western Superiority, Eastern Subordination, and Mimicry. The forms Postcolonial most found in this research are Western Superiority and Cultural Mimicry. Western superiority tends to bring out the advantages that the Western has had. While the cultural mimicry is impersonation and immitation (which is expected by English learners) to Western culture. Thus, it can be concluded that the western influences in the books are seen from the description of the positive edges and the omission of the negative sides of the West. Keywords: postkolonial, English Text Book, analysis